2010
DOI: 10.1016/j.virusres.2010.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of host cell responses and evasion strategies for porcine reproductive and respiratory syndrome virus

Abstract: The immune surveillance system protects host cells from viral infection, and viruses have evolved to escape this system for efficient proliferation in the host. Host cells produce cytokines and chemokines in response to viral infection, and among such effector molecules, type I interferons are the principal antiviral cytokines and therefore effective targets for viruses to disarm host surveillance. Porcine reproductive and respiratory syndrome virus (PRRSV) expresses proteins that circumvent the IFN response a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
118
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(121 citation statements)
references
References 150 publications
(152 reference statements)
2
118
1
Order By: Relevance
“…Th1 responses are associated to increased CD8T cell proliferation (Ekkens et al, 2007), production of opsonizing antibodies (Lefeber et al, 2003) and maximizing macrophage killing activity (Stout et al, 2005), thus providing an optimal milieu for anti-viral immunity. Importantly, the early generation of tissue-tropic effector cells induced by carbopol may counteract the immune escape mechanism evolved by PRRSV such as delayed production of neutralizing antibodies, suppression of interferon type-I IFNs, and up-regulation of IL-10 (Yoo et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Th1 responses are associated to increased CD8T cell proliferation (Ekkens et al, 2007), production of opsonizing antibodies (Lefeber et al, 2003) and maximizing macrophage killing activity (Stout et al, 2005), thus providing an optimal milieu for anti-viral immunity. Importantly, the early generation of tissue-tropic effector cells induced by carbopol may counteract the immune escape mechanism evolved by PRRSV such as delayed production of neutralizing antibodies, suppression of interferon type-I IFNs, and up-regulation of IL-10 (Yoo et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, neither traditional control strategies nor conventional vaccines achieve consistent PRRS control (4)(5)(6). A major obstacle to successful PRRS vaccine development is the inconsistent induction of protective immunity (7)(8)(9). During PRRSV infection in animals, unknown viral properties apparently allow PRRSV to persist.…”
mentioning
confidence: 99%
“…For optimal survival, some IFN-antagonistic viruses induce the activation of NFk B to facilitate the inflammatory response and the production of immunosuppressive cytokines. For example, PRRSV, a known inhibitor of IFN production that targets the RIG-I (retinoic acid-inducible gene 1) pathway (Luo et al, 2008), has been shown to activate NFk B to induce the production of pro-inflammatory cytokines (IL-6, IL-8 and TNF-a) (Lee & Kleiboeker, 2005;Yoo et al, 2010) and the immunosuppressive cytokine IL-10 ( Song et al, 2013). In this study, we observed that PBoV NP1 induced the activation of NFk B by enhancing phosphorylation of p65 and degradation of IkBa.…”
Section: Discussionmentioning
confidence: 99%